2015
DOI: 10.1007/s00432-015-1983-5
|View full text |Cite
|
Sign up to set email alerts
|

Changing incidence of myeloproliferative neoplasms: trends and subgroup risk profiles in the USA, 1973–2011

Abstract: Demographic characteristic of ET and PMF patients may be useful for improving risk prediction and informing clinical screening and treatment strategies. Changing guidelines, new discoveries, and in-depth analysis of a large population-based study have implications for accurately identifying incident cases of MPNs, MPN subgroups, and health resource planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
9
29
0
Order By: Relevance
“…The annual incidence of PV and ET was similar 1.5–1.6/100 000 persons while the incidence of PMF was as expected lower, around 0.5/100 000 persons. The incidence of PV and PMF was higher in men and ET was more common in women, which is line with earlier reports . The incidence of PV remained stable over time while there was an increase in the incidence of ET and PMF and a simultaneous decrease in the incidence of MPN‐U.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The annual incidence of PV and ET was similar 1.5–1.6/100 000 persons while the incidence of PMF was as expected lower, around 0.5/100 000 persons. The incidence of PV and PMF was higher in men and ET was more common in women, which is line with earlier reports . The incidence of PV remained stable over time while there was an increase in the incidence of ET and PMF and a simultaneous decrease in the incidence of MPN‐U.…”
Section: Discussionsupporting
confidence: 91%
“…Several investigators have assessed the incidence of MPNs in different parts of the world. The incidence of all subtypes of MPNs combined, ranges from 2–3/100 000 person‐years, occasionally up to 4–4.5/100 000 person‐years in previous studies . As for the incidence of the different MPN subtypes, a recent meta‐analysis revealed pooled figures of 0.84 PV cases, 1.03 ET cases and 0.47 PMF cases /100 000 person‐years .…”
Section: Discussionmentioning
confidence: 94%
“…[5] Since 2005, when screening of JAK2 mutation has begun, it was reported that the rates of correct ET diagnosis have increased by 31% and the rates of correct PV diagnosis have decreased by 21%. [10] In our study, the frequency of the JAK2 V617F mutation has been found 73% in PV patients, and 61% in ET, as those rates were found to be lower in PV patients compared to reported rates. [11] JAK2 mutation has been found in five of nine cases (55%) with PMF.…”
Section: Discussionsupporting
confidence: 42%
“…In 2010, the prevalence of ET, PV and MF was 134,000, 148,000 and 13,000, respectively, in the United States(2). PV and MF are more common in males, while there is a small preponderance for females in ET(3). Risk factors for the development of MPNs include white race and older age(4).…”
Section: Introductionmentioning
confidence: 99%